PERKEMBANGAN PENDIDIKAN DI DESA SIMPANG PERAK JAYA KECAMATAN KERINCI KANAN KABUPATEN SIAK (1993-2014) - Syafii, Muhammad; Isjoni, Isjoni; Saiman, Marwoto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Simpang Perak Jaya village subdistrict Kerinci kanan district Siak is transmigration villages, which are Transmigration Settlement Unit (UPT) Settlement Unit VII (SP) 7 region of Buatan Inti Indo Sawit Subur (IIS) that is included in the Office of the Ministry of Transmigration Dumai in region Bengkalis subistrict of Siak. Under district expansion according The Constituion Number 53 , 1999 about Siak District formation, and then Simpang Perak Jaya village under Kerinci Kanan Subsdistrict Siak District jurisdiction. This research have purpose for understanding (1) To determine the development of community education Simpang Kanan Perak Jaya Kerinci Subdistrict Siak Regency (1993-2014). (2) To knowing amount of of students who that have school in simpang perak jaya village (1993-2014). (3) To determine the number of educators in Simpang Perak Jaya jaya village (4) To determine the number of educational facilities in Simpang Perak Jaya village. (5) To determine the factors that influence the development of education in Simpang perak jaya village (1993-2014). This research use descriptive qualitative method with history approach and data accumulation including interview, litterature and documentation. The result of this research is showing that educational development in Simpang Perak Jaya Village increase as the educational employee is increasing the successing people development.Keywords: Education,SimpangPerak jaya Village